2011
DOI: 10.1002/jps.22680
|View full text |Cite
|
Sign up to set email alerts
|

Impact of CYP3A5*3 and CYP2C8-HapC on Paclitaxel/Carboplatin-Induced Myelosuppression in Patients with Ovarian Cancer

Abstract: Abstract:The influence of genetic variants on paclitaxel-induced toxicity is of considerable interest for reducing adverse drug reactions. Recently the genetic variants CYP2C8*3, CYP2C8-HapC, and CYP3A5*3 were associated with paclitaxel-induced neurotoxicity. We therefore investigated the impact of CYP2C8-HapC and CYP3A5*3 on paclitaxel/carboplatin-induced myelosuppression and neurotoxicity. Thirty-three patients from a prospective pharmacokinetics study were genotyped using pyrosequencing. Patients with varia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
30
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(36 citation statements)
references
References 11 publications
5
30
1
Order By: Relevance
“…We applied the same criterion to assess neuropathy in the three participating hospitals, and half of the patients went through a thorough neurologic examination 7 10. However, the limited number of samples included in our study implies reduced statistical power, making it possible that additional true associations went undetected.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We applied the same criterion to assess neuropathy in the three participating hospitals, and half of the patients went through a thorough neurologic examination 7 10. However, the limited number of samples included in our study implies reduced statistical power, making it possible that additional true associations went undetected.…”
Section: Discussionmentioning
confidence: 99%
“…Blood or saliva samples were collected from 144 cancer patients treated with paclitaxel in one Spanish and two Swedish centres: 48 patients (33%) from Hospital Universitario Fundación Alcorcón,7 63 (44%) from Karolinska University Hospital, and 33 (23%) from Linköping University Hospital 10. Eligible patients were over 18 years of age and had: received a chemotherapy regimen with paclitaxel 175 mg/m 2 and carboplatin area under the time–concentration curve (AUC) 5–6 every 21 days to treat a histologically documented solid neoplasia; life expectancy of ≥12 weeks; Eastern Cooperative Oncology Group performance status of ≤2; no chemotherapy, hormonal therapy nor radiotherapy in the 4 weeks before treatment; taken contraception (fertile women only); adequate bone marrow, renal and hepatic function; and no previous history of neuropathy.…”
Section: Methodsmentioning
confidence: 99%
“…There is a strong linkage between the functional CYP3A5*1 allele and CYP3A4*1B allele, and presence of these alleles together has been related to increased docetaxel clearance [30,31]. A few studies have reported associations between the low-activity CYP3A5*3 (6986A>G, rs776746) SNP and a lower risk of hematological toxicity in patients treated with docetaxel [39] or paclitaxel [40], however, the opposite finding has also been reported [41]. …”
Section: Pharmacogeneticsmentioning
confidence: 99%
“…Secondary analyses of three small studies [32,40,44] suggested an increase in neurotoxicity risk of patients carrying the low-activity CYP2C8*3 variant, which consists of two polymorphisms that occur in almost complete linkage disequilibrium (416G>A, R139K, rs11572080; and 1196A>G, K399R, rs10509681). This has recently been replicated in analyses of independent patient cohorts [42,45].…”
Section: Pharmacogeneticsmentioning
confidence: 99%
“…Extensive investigations are still in pursuit in search of more effective camptothecin derivative. Certain compounds such as Topotecan-developed by SmithKline Beecham (now known as Glaxo SmithKline) and Irinotecan-developed by Yakult Honsha (Japanese company); are now in therapeutic use [45,46]. Topotecan has shown effectiveness and it is extensively used for the smallcell lung cancers, while Irinotecan for the colorectal cancer treatments.…”
Section: Campothecin Derivativesmentioning
confidence: 99%